DEFORMING ORAL HABITS IN SCHOOLCHILDREN AGED 5-12 YEARS FROM THE COLOMBIA MUNICIPALITY, 2020-2022 - Morrera, Carlos Miguel Ramírez; Fernández, Ivón Abreu; Viamontes, Yuliet Sosa; Fernández, Miguel Ángel Pérez; Aguilera, Katiana Yusmila González; Pérez, Dairene Cala (International Journal of Research -GRANTHAALAYAH, 2026)
A descriptive cross-sectional study was conducted to characterize deforming oral habits in schoolchildren aged 5-12 years of age at the "Cepero Bonilla" Primary School in the municipality of Colombia, in the period from September 2020 to January 2022. The universe was made up of 62 schoolchildren enrolled in this school and the sample by 42 schoolchildren who presented some of these habits. The variables in studies were: Age groups, Sex, Deforming oral habits, frequent clinical characteristics and Classification according to frequency and intensity, which were related and statistically analyzed. Information was obtained from data provided from individual medical history and oral examination.e located checked and represented in absolute numbers and percent.